CARDIOVASCULAR SYSTEM REACTIVITY TO PHYSICAL ACTIVITY DEPENDENCE ON THE CORTISOL SALIVARY CONTENT AT CHILDREN - S. S. Sidorov; E. A. Chanchaeva; R. I. Ayzman (Сибирский научный медицинский журнал, 2019)
Aim of the study - to estimate the indicators of the central haemodynamics of children of the first class in Gorno-Altaysk when conducting one-stage functional Martinet - Kushelevsky’s test depending on the level of salivary cortisol. Material and methods. An object of the research was the students of the first class of schools No. 7, 8 and 12 of Gorno-Altaysk (78 children, including 33 boys and 45 girls in the age of 7-8 years). Content of salivary cortisol and indicators of the central haemodynamics were determined when performing one-stage functional Martinet - Kushelevsky’s test (heart rate, arterial blood pressure, systolic and minute blood volume). The type of cardiovascular system reaction, the reaction quality indicator and blood circulation efficiency were defined on the basis of restoration dynamics of heart rate and arterial pressure. Correlation analysis of cardiovascular system indicators and level of salivary cortisol was carried out. Results and discussion. Cortisol level at the examined children didn’t go beyond reference values. The normotonical type of cardiovascular system reaction to physical activity was noted at 54 % of children (42 of 78), atypical types of reaction were revealed at the others: asthenic at 38 % (30 of 78), dystonic at 6 % (5 of 78) and step-type at 1 % (1 of 78). The indicator values of reaction quality of examined children demonstrate that cardiovascular system adaptation to physical activity at children is carried out due to insignificant increase in pulse pressure and excessive increase in heart rate. The performance indicator of low circulation values are caused by significant increase in heart rate in relation to the systolic pressure (the rate of circulation value is lower than optimum level at 61 % of children). Restoration of heart rate after loading at the examined children took place for the 3rd minute however the mode of this indicator restoration is of decremental character being a sign of cardiovascular system unstable condition. The positive correlation of average degree between the salivary cortisol level and HR indicators of both after physical activity and during restoration is revealed ( p < 0,05). Therefore, the cardiovascular system of children with rather high rates of free cortisol in saliva is notable for the bigger reactivity to physical activity. Conclusion. The atypical type of cardiovascular systems reaction to standard physical activity and the decremental nature of HR restoration is revealed at 46 % examined children of the first class of general education institutions No. 7, 8 and 12 of Gorno-Altaysk. The significant increase in HR after physical activity is revealed at children with higher level of salivary cortisol.